Alpha 5 subunit-containing GABAA receptors in temporal lobe epilepsy with normal MRI. Issue 1 (2nd January 2021) - McGinnity, Colm J; Barros, Daniela A Riaño; Hinz, Rainer; Myers, James F; Yaakub, Siti N; Thyssen, Charlotte; Heckemann, Rolf A; de Tisi, Jane; Duncan, John S; Sander, Josemir W; Lingford-Hughes, Anne; Koepp, Matthias J; et al.
Abstract: GABAA receptors containing the α5 subunit mediate tonic inhibition and are widely expressed in the limbic system. In animals, activation of α5-containing receptors impairs hippocampus-dependent memory. Temporal lobe epilepsy is associated with memory impairments related to neuron loss and other changes. The less selective PET ligand [ 11 C]flumazenil has revealed reductions in GABAA receptors. The hypothesis that α5 subunit receptor alterations are present in temporal lobe epilepsy and could contribute to impaired memory is untested. We compared α5 subunit availability between individuals with temporal lobe epilepsy and normal structural MRI ("MRI-negative") and healthy controls, and the relationship of α5 subunit availability with episodic memory performance, in a cross-sectional study. Twenty-three healthy male controls (median±interquartile age 49 ± 13 years) and 11 individuals with MRI-negative temporal lobe epilepsy (seven males; 40 ± 8) had a 90-minute PET scan after bolus injection of [ 11 C]Ro15-4513, with arterial blood sampling and metabolite correction. All those with epilepsy and six controls completed the Adult Memory and Information Processing Battery (AMIPB) on the scanning day. "Bandpass" exponential spectral analyses were used to calculate volumes-of-distribution separately for the fast component (VF ; dominated by signal from α1 (α2, α3)-containing receptors) and the slow component (VS ; dominated by signal from α5-containing receptors). We made voxel-by-voxel comparisons between: the epilepsy and control groups; each individual case versus the controls; and epilepsy subgroups based on memory scores. We obtained parametric maps of VF and VS measures from a single bolus injection of [ 11 C]Ro15-4513. The epilepsy group had higher VS in anterior medial & lateral aspects of the temporal lobes, the anterior cingulate gyri, the presumed area tempestas (piriform cortex), and the insulae, in addition to increases of ∼24% and ∼26% in the ipsilateral and contralateral hippocampal areas (p < 0.004). This was associated with reduced VF : VS ratios within the same areas (p < 0.009). Comparisons of VS for each individual with epilepsy versus controls did not consistently lateralise the epileptogenic lobe. Memory scores were significantly lower in the epilepsy group than in controls (mean± standard deviation -0.4 ± 1.0 versus 0.7 ± 0.3; p = 0.02). In individuals with epilepsy, hippocampal VS did not correlate with memory performance on the AMIPB. They had reduced VF in the hippocampal area which was significant ipsilaterally (p = 0.03), as expected from [ 11 C]flumazenil studies. We found increased tonic inhibitory neurotransmission in our cohort of MRI-negative temporal lobe epilepsy who also had co-morbid memory impairments. Our findings are consistent with a subunit shift from α1/2/3 to α5 in MRI-negative temporal lobe epilepsy. Graphical Abstract: